Nonmotor Features in Parkinson's Disease: What Are the Most Important Associated Factors?. (19th April 2016) - Kadastik-Eerme, Liis; Muldmaa, Mari; Lilles, Stella; Rosenthal, Marika; Taba, Nele; Taba, Pille
Abstract : Introduction . The purpose of this study was to demonstrate the frequency and severity of nonmotor symptoms and their correlations with a wide range of demographic and clinical factors in a large cohort of patients with Parkinson's disease (PD). Methods . 268 PD patients were assessed using the validated Movement Disorders Society's Unified Parkinson's Disease Rating Scale (MDS-UPDRS), the Beck Depression Inventory (BDI), Parkinson's Disease Questionnaire (PDQ-39), the Hoehn and Yahr scale (HY), the Schwab and England Activities of Daily Living (SE-ADL) Scale, and the Minimental State Examination (MMSE). Results . Nonmotor symptoms had a strong positive relationship with depression and lower quality of life. Also, age, duration and severity of PD, cognitive impairment, daily dose, and duration of levodopa treatment correlated with the burden of nonmotor symptoms. Patients with postural instability and gait disorder (PIGD) dominance or with the presence of motor complications had higher MDS-UPDRS Part I scores expressing the load of nonmotor features, compared to participants with other disease subtypes or without motor complications. Conclusions . Though the severity of individual nonmotor symptoms was generally rated by PD patients as "mild" or less, we found a significant cumulative effect of nonmotor symptoms on patients' mood, daily activities, and quality of life.